[Dr. Gundelina Velazco spoke on psychotherapy of the abused child and family] - Velazco, Gundelina A. (Animo Repository, 1997)
Dr. Gundelina Velazco of the Psychology Department spoke on Psychotherapy of the abused child and family focusing on the insight, relationship, and curative therapies that can be used to deal with the consequences of abuse.